Valorization of waste biomass from oleaginous "oil-bearing" seeds through the biocatalytic production of sinapic acid from mustard bran. (February 2021) - Achinivu, Ezinne C.; Flourat, Amandine L.; Brunissen, Fanny; Allais, Florent
Abstract: This paper focuses on developing a sustainable and integrated process for the biocatalytic extraction of sinapic acid from the waste biomass of oleaginous "oil-bearing" seeds. Using an optimized chemo-enzymatic technique, sinapine was effectively liberated from mustard bran and then completely hydrolyzed into sinapic acid. Several parameters were optimized to release sinapic acid ( e.g., mustard species, extraction methods, mustard production dates, ethanol concentration, solids loading, extraction time and enzyme type or concentration). Subsequently, an integrated bioprocess was developed and scaled up guided. The results revealed that the biomass type or source and the enzyme used can substantially impact the release of sinapic acid, and overall cost, respectively. For the Canadian lot of crude mustard bran, 10 mg of sinapic acid per g mustard bran was successfully extracted, along with 43 mg total phenolics per g mustard bran and 71 mg sugars per g mustard bran. Lastly, supplementary portions of the biomass ( i.e., lipids) were also discussed for their applicability as value added products. Graphical abstract: Image 1 Highlights: Waste biomass from oil seeds is a direct source of biobased phenolic (sinapic) acid. Enzymes can biocatalyze the release of sinapic acid (SA) from mustard bran yielding up to 10 mg of SA per g mustard bran. Enzymatic cocktails with esterases are the most effective (> 90% yield of SA), but they can be substrate specific. Sinapic acid yields are dictated by the biomass type, harvest year and solid load. The optimized bioprocess can be consolidated (into one pot) and scaled up effectively. Abstract : Naturally occurring bioactive molecule (sinapic acid) was extracted from mustard bran using a sustainable chemo-enzymatic method.